Groundwater quality and origin within Dibdibba aquifer, near Jabel Sanam area southern of Basrah Governorate, Iraq - Al-Tememi, M.K. (Mesopotamian Journal of Marine Sciences, 2022)
The study aims at assessing the groundwater quality and identifying its origin within the Dibdibba aquifer (Jabel Snam area) south of Basrah. Twenty wells were selected from the studied area and subjected to comprehensive physical and chemical analyses involving major cations (Ca2+, Mg2+, Na+ and K+), anions (HCO3-, Cl- and SO42-) and trace elements (Zn, Cd, Ni and Pb) besides general parameters (pH, EC, TDS and total hardness). The spatial distribution of parameters were drawin using geostatistic, interpolation technique, namely, ordinag Kriging in Arc GIS 10.2.2. Based on the results, the groundwater quality was classified to chloride group-sodium family-type (Na+ >Ca2+ >Mg2+). On the other hand, the groundwater origin investigated by Sullin diagram which showed old meteoric origin for all the studied wells.